Tata Kelola Keuangan dan Penyusunan Anggaran Pendapatan dan Belanja Kalurahan : Studi di Kalurahan Poncosari Kabupaten Bantul Tahun Anggaran 2025 - Dita Prihartati; Fadhila Atika Najmi; Salma Abinawa Nurra Majid (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Village governance plays an important role in supporting the effectiveness of development planning and improving community welfare. This study aims to analyze financial management governance and the process of preparing the Village Revenue and Expenditure Budget (APBKal) in Kalurahan Poncosari, Bantul Regency, for the 2025 fiscal year. This research employs a qualitative approach using a case study method, involving in-depth interviews with key informants and documentation analysis of relevant regulations and financial reports. The results show that financial management in Kalurahan Poncosari has been implemented systematically through the stages of planning, implementation, administration, reporting, and accountability in accordance with applicable regulations. The planning process is conducted in a participatory manner through tiered community deliberations, such as hamlet-level deliberations and village development planning deliberations, involving residents. In addition, the use of digital systems such as E-RAB and Siskeudes supports transparency and administrative order. However, challenges remain, including limited budget flexibility due to mandatory programs from central and regional governments, limited human resource capacity, and shifts in community participation patterns. In conclusion, the governance of APBKal in Kalurahan Poncosari demonstrates compliance and accountability; however, improvements in administrative capacity and fiscal flexibility are needed to better respond to community needs.